The Effect of Work Life Balance and the Implementation of Knowledge Management on the Performance of Educational Staff at Universitas Jenderal Achmad Yani - Prabaning Dyah Sawitri; Mochamad Vrans Romi (Journal of General Education and Humanities, 2026)
This research addresses the issue of suboptimal educational staff performance in higher education institutions, which is often associated with imbalances between professional and personal life and ineffective organizational knowledge practices. The study aims to analyze the influence of work-life balance and the implementation of knowledge management on the performance of educational staff at Universitas Jenderal Achmad Yani. A quantitative research design grounded in a positivist paradigm was employed. Data were obtained through semantic differential scale questionnaires, supported by observations, interviews, and secondary sources from relevant literature. From a population of 600 educational staff members, 100 respondents were selected using the Slovin formula and purposive sampling. The data were examined using descriptive and associative statistical analyses. The findings reveal that work-life balance, knowledge management implementation, and staff performance are generally perceived as moderate. Partially, work-life balance has a positive effect on educational staff performance, while knowledge management implementation also shows a stronger positive influence. Simultaneously, both variables significantly affect the performance of educational staff. These results highlight that strengthening work-life balance policies and optimizing knowledge management systems are crucial for improving the performance of educational staff in the university context.